(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
„Business is the only mechanism on the planet today powerful enough to produce the changes necessary to reverse global environmental and social degradation” (Paul Hawken). This idea characterizes the substance of the paper exactly. The paper presents results of 24 different enterprises survey in the Latvia eastern region Latgale on their present-day situation in the field of environment protection, awareness of their responsibility and their planned innovation activities in the implementation pollution prevention technologies.